Determining target engagement in living systems - Simon, Gabriel M. (2013)
Chemical probes are critical tools for elucidating the biological functions of proteins and can lead to new medicines for treating disease. The pharmacological validation of protein function requires verification that chemical probes engage their intended targets in vivo. Here we discuss technologies, both established and emergent, for measuring target engagement in living systems and propose that determining this parameter should become standard practice for chemical probe and drug discovery programs.